Web-based science communication at Research Institute level: balancing dissemination, dialogue and promotion in a major Italian scientific institution - Giuffredi, Rita; Grasso, Valentina; L’Astorina, Alba (Frontiers in Communication, 2024)
This study examines the online communication practices of research institutes affiliated with the Italian National Research Council. The analysis employs a combination of quantitative and qualitative methods to evaluate whether these institutes leverage digital technologies to transition from a unidirectional, strategic approach to communication towards a more dialogic and engaging approach with the public. Specifically, the study analyses the institutes' websites, assessing their use of communication tools, content, target audience, knowledge flows, and contextualization of communication activities, while also highlighting disciplinary-based differences. Although recent research identified Research Institutes' level as a promising ground for research communication to flourish, our study suggests that, on average, they still employ digital technologies in the same way as traditional media, disseminating information about institutional advancements rather than fostering interactive dialogue. Communication styles remain grounded in dissemination and strategic models, which restricts the ability of research institutes to develop a dynamic and transformative relationship with society.